Towards a common vision of climate, peace, and security in Ethiopia - Villa, Victor; Singh, Radhika; Chepngetich, Brenda; Takaindisa, Joyce; Pacillo, Grazia (2025)
Ethiopia faces compounding climate, peace, and security challenges that are intensifying pre-existing socio-economic vulnerabilities and institutional weaknesses. The impacts of climate variability, prolonged droughts, erratic rainfall, and land degradation, are particularly severe in rural areas reliant on natural resources, leading to rising displacement, food insecurity, and local conflicts over land and water. Climate-induced stressors are also reshaping urbanization trends, migration patterns, and social cohesion, further straining fragile governance systems. In this context, CGIAR’s Focus Climate Security team, in collaboration with UNECA and other key partners, convened a two-day workshop in Addis Ababa to foster a common vision for integrated action across the climate, peace, and security nexus. Bringing together over 45 national and international experts from government, UN agencies, NGOs, and academia, the workshop explored opportunities for evidence-based policy alignment, long-term investment in resilience, and locally grounded responses. Through participatory methods, including a Three Horizons exercise, participants outlined institutional reforms, anticipatory early warning systems, and durable solutions for displacement that center equity, inclusion, and sustainability as core pillars of Ethiopia’s climate-secure future.